ISR meets SAR outside: additive action of the endophyte Bacillus pumilus INR7 and the chemical inducer, benzothiadiazole, on induced resistance against bacterial spot in field-grown pepper - Yi, Hwe-Su; Yang, Jung Wook; Ryu, Choong-Min (Frontiers in Plant Science, 2013)
Induced resistance has been recognised as an attractive tool for plant disease management in modern agriculture. During the last two decades, studies on chemically- and biologically-elicited induced resistance have revealed previously unknown features of the plant defence response including defence priming. As a biological trigger for induced resistance, plant growth-promoting rhizobacteria (PGPR) are a group of root-associated bacteria that can reduce plant disease severity and incidence, and augment plant growth and yield under greenhouse and field conditions. We evaluated the potential of an endophytic PGPR, Bacillus pumilus INR7, to induce systemic resistance against bacterial spot caused by Xanthomonas axonopodis pv. vesicatoria in pepper. Trials in the greenhouse showed significantly less symptom development in pepper plants inoculated with strain INR7 compared to a water treatment. Furthermore, a single dipping treatment with INR7 before transplantation of pepper plants into the field elicited an induced systemic resistance (ISR) response against bacterial spot caused by artificially infiltration of X. axonopodis pv. vesicatoria and even against naturally occurring bacterial spot disease. We identified an additiveeffect on induced resistance after administration of a combination treatment composed of strain INR7 with a chemical inducer, benzothiadiazole (BTH) in the field. The combination treatment stimulated expression of pepper defence marker genes CaPR1, CaTin1, and CaPR4 to a greater extent than did treatment with either agent alone. Similar experiments conducted with tobacco revealed no additive effects under field conditions. Interestingly, co-application of plants with INR7 lifted the growth repressing effect of BTH. Application of benzothiadiazole onto pepper and tobacco did not affect rhizosphere colonisation but supported a higher population density inside plant roots when compared to water-treated control plants. Our results indicate that PGPR can